The Historical Changes of the Image of Toyohiko Kagawa in China during the Period of the Republic of China (1925-1941): Centered on the Report of The China Press - YU, Lingfeng (Journal of Research for Christianity in China (JRCC), 2025)
This article compiled 58 reports of The China Press about the Japanese social activist and Christian leader Who is called Toyohiko Kgawa in The China Press in detail, exploring the historical changes in the evaluation of Kagawa and his friendship situation in China. The article mainly discussed the report about Kagawa in the China Press in three periods as follow: 1) The first reported time to the Mukden Incident(1925-1931); 2) the Mukden Incident to the Lugou Bridge Incident (1931-1937); 3) After the Lugou Bridge Incident (1937-1941). First of all, this papaer focused on the exchanges between Kagawa and the Shanghai American Alumni Association in 1930, revealing the process of Kagawa’ effort to build the context of Sino-Japanese-American communication. Secondly, The paper analyzed Kagawa’s apology to the Chinese for Japan’s actions in China and expoled views of The China Press on him. In addition, This papaer investigated the oppositive relationship between Kagawa and Chinese Christian leaders in the United States in 1936. By analyzing the reports of The China Press on Kagawa, not only filled the gaps in Kagawa’s study, but also helped to explore the role of Japanese Christian leaders’ efforts to peace in modern times. The efforts made in the history of Sino-Japanese exchanges have provided a new perspective for exploring the history of Christian exchanges in Northeast Asia.